EFFECT OF BI RATE, INFLATION, EXCHANGE, AND THE DOW JONES AGAINST COMPOSITE STOCK PRICE INDEX (CSPI CASE STUDY IN 2009-2014) - Tuti Purwaningsih (Jurnal Ekonomi Pembangunan, 2015)
The purpose of this study was to determine the influence of the independent variables are indicated by the BI Rate, the rate of inflation, exchange rate and the Dow Jones Against Composite Stock Price Index. The analysis tool used is multiple linear regression using time series data is 2009-2014. In the model equations, Composite Stock Price Index is the dependent variable and the BI Rate, the rate of inflation, exchange rates as well as Dow Jones is the independent variable. Results of regression is that the variable BI Rate (X1) a significant negative effect on the Composite Stock Price Index, inflation (X2) significant negative effect on the Composite Stock Price Index, the exchange rate (X3) significant negative effect on Stock Price Index and Index Dow Jones (X3) positive and significant impact on the Composite Stock Price Index. The coefficient of determination (R2) is 0.970445, or 97%. This indicates that the BI Rate (X1), the rate of inflation (X2), the exchange rate (X3) and Dow Jones (X4) in explaining the dependent variable or dependent Composite Stock Price Index amounted to 97%, while the remaining 3% is explained by other variables outside the model that implicitly reflected in confounding variables.  Suggestions can meet of the results of this study are advised to look at the effect of other macroeconomic variables in detail which can affect and use other variables outside the monetary variables like social and political situation of a country. And also advised to conduct research using other approaches.